Ultrarapid and ultrasensitive electrical detection of proteins in a three-dimensional biosensor with high capture efficiency1. Issue 21 (7th June 2015) - Kim, Bo-Yeong; Sohn, Il-yung; Lee, Doowon; Han, Gill Sang; Lee, Won-Il; Jung, Hyun Suk; Lee, Nae-Eung
<x xml:space="preserve">Abstract</x> A bio-FET using 3D sensing channel structures composed of ZnO nanorods and graphene demonstrates the capability of achieving ultrarapid and ultrasensitive immunodetection.